Investment and bank credit recovery after banking crises - Teimouri, Sheida; Dutta, Nabamita (Journal of Financial Stability, 2016)
In this paper, we aim to investigate (a) the dynamic adjustment of investment-to-GDP ratio and bank credit-to-GDP ratio following banking crisis episodes; (b) whether the adjustment of investment and bank credit ratios varies with several country and crisis characteristics. Based on a sample of 79 developed and emerging countries over the 1973–2010 period, our results suggest that in the aftermath of banking crises, investment ratio declines but swiftly recovers to its pre-crisis level within two to three years. Bank credit declines significantly and remains stagnated even in the medium run. In terms of country characteristics, we find that investment and bank credit ratios decline significantly more in advanced countries and countries with higher level of capital openness. In addition, investment ratio declines significantly more in countries with higher level of financial development. Finally, we split the banking crises episodes into two categories: those preceded by a domestic credit boom or a surge in net capital inflows, and those that were not preceded by such booms. We find that dynamic adjustment of investment and bank credit ratios differs substantially across the two groups. Existence of a credit boom or a surge in capital inflow in the run-up to the crisis intensifies the length and depth of the decline in investment and bank credit ratios. In fact, we find no statistically significant decline in investment following banking crises that were not preceded by a credit boom or a surge in capital inflows. These results imply that deleveraging is costly to the economy.